2022
DOI: 10.1111/jonm.13647
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and intent to leave during COVID‐19: A cross‐sectional study of New Jersey hospital nurses

Abstract: Aim The aim of this work is to examine staffing, personal protective equipment (PPE) adequacy and physical exhaustion that contributed to burnout and intent to leave among hospital nurses during the first peak of the COVID‐19 pandemic. Background Burnout is associated with adverse nurse and patient outcomes. Identifying the magnitude of burnout that occurred during the pandemic can prepare managers for the long‐term mental health effects on nurses. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
(37 reference statements)
1
28
0
Order By: Relevance
“…This result may be due to the nature of the profession, which allows nurses to function and even refine their competency under constant occupational pressure and stress. Studies on burnout levels of nurses have shown that this population of health care professionals constantly has moderate levels of burnout due to the complex nature of their occupation (Ali Zakeri et al, 2020 ; de Cordova et al, 2022 ; Jose et al, 2020 ). With such a level of burnout, workload and other factors may be manageable and even provide an avenue for nurses to enhance their decision‐making skills and clinical skills, thus, their overall nurse competence (Afshar et al, 2020 ; Mudallal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be due to the nature of the profession, which allows nurses to function and even refine their competency under constant occupational pressure and stress. Studies on burnout levels of nurses have shown that this population of health care professionals constantly has moderate levels of burnout due to the complex nature of their occupation (Ali Zakeri et al, 2020 ; de Cordova et al, 2022 ; Jose et al, 2020 ). With such a level of burnout, workload and other factors may be manageable and even provide an avenue for nurses to enhance their decision‐making skills and clinical skills, thus, their overall nurse competence (Afshar et al, 2020 ; Mudallal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study was conducted during the COVID‐19 pandemic, a period during which frontline nurses are facing significant difficulties in carrying out their nursing roles and responsibility. Published studies on burnout during the COVID‐19 pandemic reported burnout's influence on nurses' intention to leave (de Cordova et al, 2022 ), burnout during the first wave of the pandemic (Galanis et al, 2021 ; Khan et al, 2022 ), burnout on quality patient care (Kakemam et al, 2021 ), burnout and the affective aspect of nurses (Falatah & Alhalal, 2022 ), burnout's burden to nurses' roles (Kishi et al, 2022 ) and burnout's relationship to self‐efficacy (Lim et al, 2022 ). None of these published studies focused on the moderating effect of burnout on nurses' professionalism, values and competence.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the impact of the subject under analysis, which has been demonstrated in several studies, one of the highlighted aspects is the extreme physical and emotional demands requested from nurses. It is not surprising that there has been a growing number of studies on this topic about the magnitude of burnout during the pandemic because of the increased demand from all professionals [ 35 , 36 , 37 ]. That is why it is necessary to know this reality and create mechanisms that minimize its impact so that we are prepared as much as possible to respond to it, especially in situations where its incidence increases considerably [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, nursing staff might have to take on new roles to meet the surge in demand. Recent research demonstrates that hospital staff experienced burnout during the peak of the pandemic [ 27 , 28 ]. Low staffing levels are among the critical predictors of staff burnout [ 24 ].…”
Section: Introductionmentioning
confidence: 99%